Exploring the Impact of Informal Practices on Social Exclusion and Age‐Friendliness for Older People in Rural Communities. (January 2014) - Walsh, Kieran; O′Shea, Eamon; Scharf, Thomas; Shucksmith, Mark
ABSTRACT This article explores the role of informal practices, across the state, private, voluntary, and family and friend systems, in addressing social exclusion in rural communities in Ireland and Northern Ireland. In doing so, we examine the relevance of the 'age‐friendly' concept to rural settings. Using focus group discussions, involving 62 community stakeholders from 10 communities across the two jurisdictions, we explore the four systems and their limitations in the communities and the informal practices that underlie system interactions and older adult supports and engagement. Informal practices, such as cooperative working between system actors and the performance of tasks outside professional and organisational remits, were found to underpin many community responses to supporting older people and arose from collective interdependencies, the multiplicity of individual roles (e.g. professional, community member and volunteer) and positions of need. Informal practices strengthened the capacity of these rural communities to address social exclusion of older people and enhanced local aspects of age‐friendliness. The findings are discussed in light of the diversity of rural older people and their communities, transformative process of change and the need for a more nuanced understanding of age‐friendliness in rural settings. Copyright © 2013 John Wiley & Sons, Ltd.